Development of "ATAP" (Al Qur'an therapy to answer the problem) in improving self-compassion and resilience of parents of children with special needs - Astutik, Anita Puji; Nordin, Nadhirah; Hasanudin, Cahyo; Fitroh, Siti Fadjryana; Azizah, Nuril Lutvi; Meilinda, Isna; Rahma, Aulia (Edelweiss Applied Science and Technology, 2024)
The purpose of this research is to develop and test the Al-Quran Therapy to Answer the Problem (ATAP) therapy model against the low value of resilience and self- compassion owned by parents of children with special needs. This research uses a type of development research or Research and Development (R&D) with the ADDIE approach. With the number of samples being 30 parents of children with special needs taken using in-depth interview techniques Focus Group Discussion (FGD), observation, and documentation at PKBM Lentera Fajar Indonesia, Sidoarjo. The development of the ATAP model is designed in accordance with the circumstances of parents of children with special needs who lack the value of resilience and self-compassion in themselves and the features presented will be wrapped in a simple way so that it will be easier for parents of children with special needs to access it. The test results from the use of ATAP found that parents of children with disabilities were greatly helped by the therapies presented, ranging from reading Quranic commentaries related to their situation, listening to and viewing motivational videos or lectures from ustadz and even being helped by the additional reminder notifications to read the Quran. The effect of using ATAP will increase the value of resilience and self-compassion of parents of children with disabilities and can get out of all the pressure, stress, high anxiety and fear that has been haunting the minds of parents of children with special needs.